The Negative Effects Questionnaire: psychometric properties of an instrument for assessing negative effects in psychological treatments. Issue 5 (15th March 2019) - Rozental, Alexander; Kottorp, Anders; Forsström, David; Månsson, Kristoffer; Boettcher, Johanna; Andersson, Gerhard; Furmark, Tomas; Carlbring, Per
Abstract: Background: Psychological treatments provide many benefits for patients with psychiatric disorders, but research also suggests that negative effects might occur from the interventions involved. The Negative Effects Questionnaire (NEQ) has previously been developed as a way of determining the occurrence and characteristics of such incidents, consisting of 32 items and six factors. However, the NEQ has yet to be examined using modern test theory, which could help to improve the understanding of how well the instrument works psychometrically. Aims: The current study investigated the reliability and validity of the NEQ from both a person and item perspective, establishing goodness-of-fit, item bias, and scale precision. Method: The NEQ was distributed to 564 patients in five clinical trials at post-treatment. Data were analysed using Rasch analysis, i.e. a modern test theory application. Results: (1) the NEQ exhibits fairness in testing across sociodemographics, (2) shows comparable validity for a final and condensed scale of 20 instead of 32 items, (3) uses a rating scale that advances monotonically in steps of 0 to 4, and (4) is suitable for monitoring negative effects on an item-level. Conclusions: The NEQ is proposed as a useful instrument for investigating negative effects in psychological treatments, and its newer shorter format could facilitate its use in clinical and research settings. However, further research is needed to explore the relationship between negative effects and treatment outcome, as well as to test it in more diverse patient populations.